O dinheiro público pelo ralo: ensaios em gestão e corrupção - Costa, Caio César de Medeiros (2016)
Efficiency managing public resources has become an important issue for the academy and for public managers. The importance of the allocative function of the state, and the increased demands of the population also, has elevation the efficiency in the public money management subject to a high degree of relevance. To contribute to this debate, the main objective of this thesis is to understand the waste of the public resource and its nuances. In such set, public procurement processes and the occurrence of corruption are two important issues asking for further strength, and it is about them that I put effort over to answer the issues raised. Thus, this thesis was organized containing three original articles. Each one of them is dedicated to a specific aspect, identified within the theories that permeate the debate in the context of public administration and government. The first article aims to analyze the relevance of public bidding processes. Based on the assumptions of the theory of auctions, highlighting the relationship between increasing competition and lower prices from the bidders, the study adds to the literature on aspects such as transaction costs and problems related to the provider definition based in price as the unique criterion. The second article discusses the relationship between the lower prices strategies on the bidding stage and the contract modifications during its execution. This article has the literature is based on the literature that pointing, the difficulties in designing complete contracts considering the possibility of bidders avail themselves of information asymmetry to plot their strategies. By this use is given the unbalanced bids name and is on the point that the second paper discuss. In the third article, the theme addressed is corruption, and the intention of it is to verify the association between corruption and public health indicators in Brazilian municipalities. The findings raise some debate and add to the state of the art issues not raised yet. Among these issues, there is an association between conducting bidding processes and prices, on average, higher. Another important issue concerns the factors related to modifications of contracts, finding no empirical evidence to demonstrate the existence of the unbalanced bid. Finally, this last article highlights the relationship between corruption and socioeconomic indicators, showing, among other things, the correlation of corruption with the indicators in the opposite direction for certain indicators. It is hoped that this thesis will stimulate further research, involving issues addressed here, ideally giving contributions to improving public management in Brazil.